ULTRASTRUCTURE OF ALVEOLAR MACROPHAGES IN CASE OF EXPERIMENTAL ACUTE RENAL FAILURE - Zaiats, L.M.; Klishch, I.P. (World of Medicine and Biology, 2018)
We have done experiments on Vistar line white male rats using electronic microscope method and studied in dynamics (12, 24, 72 hours) the ultrastructural changes of alveolar macrophages in case of experimental acute renal failure. It has been established that already in 12 hours after beginning of the experiment one can observe increase of quantity and functional activity of macrophage cells. With expansion of experimental timeline (24-72 hours), we have observed both dystrophic-destructive and adaptive changes in the alveolar macrophages.